QUR’ANIC AND SCIENTIFIC CONCEPT OF HYDROLOGY AND BOTANY A RESEARCH AND ANALYTICAL REVIEW - Prof.Dr. Naseer Ahmad Akhtar; Hafiz Muhammad Azhar Usama; Dr.Shamaila Asad; Prof .Dr.Mohamed Ibrahim Mohammad Elhalawani; Dr.Shams Tabraiz, Dr.Naima Hassan; Muhammad Rashid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This article is a large collection of discussions on the Qur’anic and scientific concept of hydrology and botany as a research and analytical review and a discussion of the various aspects arising out of the resulting. The style of this research paper will be narrative. A review of the literature has shown that science has confirmed that information and revelations about modern hydrology and botany are well described in the Qur’an. More than a thousand verses of the Qur’an provide information about modern science. And dozens of verses in it speak only of marine and botanical. The facts on this subject in the Qur’an are in complete agreement with modern science, many scientists are concerned about the current state of the earth and the crises it faces, and generally research the facts that are linked to human survival. From a scientific point of view, the resources that man needs the most are available in abundance on this planet and science is the means to reach these sciences. Explain in the light of science. Readers of this research paper will benefit from the heavenly and scientific sciences. This will make the reality of creation clear. The Holy Qur’an is a repository of knowledge and knowledge. As the human mind evolves from age to age, so will the mysteries of the Book of Allah be revealed? Science presents its results on the basis of experiments and observations. Mankind itself has been repeatedly invited to observe and experience. In this vast universe, the phenomena of nature and the wonders of nature are spread everywhere. Science is an important means for their utilization. Many wonders and phenomena of nature are mentioned in the Holy Qur’an, the important role of science has been and will continue to come to the fore, and so scientific research can help in understanding the Qur’an.